Betting against betting against beta - Novy-Marx, Robert; Velikov, Mihail (Journal of Financial Economics, 2022)
Frazzini and Pedersen’s (2014) Betting Against Beta (BAB) factor is based on the same basic idea as Blacks’(1972) beta-arbitrage, but its astonishing performance has generated academic interest and made it highly influential with practitioners. This performance is driven by non-standard procedures used in its construction that effectively, but non-transparently, equal weight stock returns. For each dollar invested in BAB, the strategy commits on average $1.05 to stocks in the bottom 1% of total market capitalization. BAB earns positive returns after accounting for transaction costs, but earns these by tilting toward profitability and investment. Predictable biases resulting from Frazzini and Pedersen’s non-standard beta estimation procedure drive results presented as evidence supporting BAB’s underlying theory.